Explaining Causes Behind SQL Query Formulation Errors - Taipalus, Toni (Proceedings - Frontiers in Education Conference, 2020)
This Full Research Paper presents the most prominent query formulation errors in Structured Query Language (SQL), and maps these errors to their cognitive explanations. Understanding query formulation errors is a key to teaching SQL. more effectively. However, studies on what kind of errors novices struggle with are relatively scarce when compared to, for example, programming languages. Although committing errors is a crucial part in learning, some errors are relatively easy to fix, and their commonness is not necessarily an indication of their difficulty. Other errors, however, halt the learning process, and are never fixed by the query writer. Using a previously established error taxonomy and queries from four cohorts with a total of 987 students, we set out to identify common errors which students are unable to correct, i.e., errors that are likely to cause query formulation failures. Our results indicate that on a general level, logical errors are the most common cause for query formulation failures, while syntax and semantic errors are usually fixed by query writers. Although query concepts, for example, expressions, joins and grouping, have a strong influence on what types of errors are committed, some errors are common regardless of query concepts. Specifically, our results indicate that missing expressions, extraneous or omitted grouping columns, incorrect comparison operators, missing joins, and missing ordering columns are the most common errors that novices are unable to fix. Based on the results, we speculate on the reasons behind the most common persistent errors using previously identified cognitive explanations. Finally, we present that solutions for mitigating the causes behind query formulation errors are already available. In order to more effectively teach query formulation, educators should emphasize natural language patterns, query planning, and increasingly ambiguous exercises.